Plan estratégico para el desarrollo institucional de la cooperativa de ahorro y crédito Juan Pio de Mora agencia Quevedo, periodo 2015-2019 - Murillo Barboza, Cindy Katherine (2015)
This investigation project consists of an introduction that will provide us with preliminary information on what the development of research will be, a goal that can develop a strategic plan to serve as a supporting tool for the development of the institution allowing this way to improve the management of its business activities. Companies must have a strategic plan, according to their sizes, and even every person should have the plan because it is the instrument to see the direction we should take clearly to achieve our goals. It is a tool that will facilitate to capture the way forward objectively; setting the vision and mission of the organization and commitment of the objectives pursued. This research was developed in the city of Quevedo, and began with the formulation of the problem tom investigate. The problem was oriented on how to develop an institutional development strategic plan for the Savings and Credit Cooperative Juan Pio de Mora. Deductive, inductive and analytical methods for the development of the objectives of this research, the have been applied. The primary and secondary sources, observation, field work consisted of applying the manager, employees and customers of the cooperative a survey in order to know their criteria. The analysis of the results allowed us to establish a strategic plan that serves the manager to take appropriate decisions to optimize the management quality by considering those suggestions. It is concluded that it is very important to have a strategic plan for the proper development of the cooperative. It was recommended that strategies need to be applied by employees in each department when appropriate.